PENINGKATAN KEMAMPUAN MENULIS KALIMAT SEDERHANA MELALUI PICTURE AND PICTURE PADA SISWA KELAS II SDN MALASAN WETAN II - Ahmad Fawardi; Didit Yulian Kasdriyanto; Ludfi Arya Wardana (STKIP Subang, 2026)
This research aims to improve students' ability to write simple sentences through the application of the Picture and Picture learning model. The study was motivated by the low writing skills of grade II students at SDN Malasan Wetan II, where 60% of students struggled to construct basic sentences. This classroom action research was conducted in two cycles following the Kemmis and McTaggart design, involving 39 students. Data were collected through written tests and classroom observations, then analyzed using descriptive quantitative and qualitative methods. The results indicate that the Picture and Picture model effectively enhances students' writing skills. The average class score increased from 56.03 in the pre-cycle to 79.10 in the first cycle, and further to 86.54 in the second cycle, with 89.74% classical mastery achieved. The use of serial pictures provided concrete visual stimuli that helped students structure their thoughts logically, specifically in mastering Subject-Predicate sentence patterns. It is concluded that the model successfully addresses the learning barrier, and it is recommended that teachers utilize diverse visual media and provide consistent positive reinforcement to maintain student engagement in early-grade literacy learning.